The Ph.D.-candidate as an information literate resource: developing research support and information literacy skills in an informal setting - Daland, Hilde (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2013)
This article aims at suggesting a new way of developing research support for PhD-candidates. Previous research on the field of research support greatly focuses on the librarians’ competencies and how to assist researchers with what they lack in information literacy (IL) skills. There is little focus on collaboration with researchers to achieve a mutual learning outcome in regard to developing research support and IL skills. A socio-cultural view on IL indicates that IL skills are developed in a context, and therefore are situated. A high level of IL in one situation could be regarded as insufficient in another. Therefore, a librarian’s view on IL could be incomparable to a PhD-student’s everyday information needs. Many liaison librarians do not have a PhD, but are still expected to provide PhD-candidates with research support of high quality. How can we do so if we only see the librarian’s perspective? Can informal settings and user involvement be a productive way of developing research support and IL skills? As librarians it is not always easy to know what researchers need. However, if the threshold has been lowered, in an informal setting, one might obtain the questions that reveal difficulties for researchers when it comes to library services and resources. Also, through user involvement, the researchers can teach librarians about the research process. This study includes an anonymous survey among PhD-candidates at the Faculty of Humanities and Education at the University of Agder (UoA) and interviews with two of the PhD-candidates in addition to interviews with all of Agder University Library’s (AUL) liaison librarians. In general, PhD-candidates that interact informally with their liaison librarian have a higher confidence in their own overview when it comes to library resources. They do not have problems contacting their librarians for help, but they do not expect the librarians to do their searching for them.